Self-esterification of partially maleated castor oil using conventional and microwave heating - Mazo, Paula (2012)
The self-esterification of partially maleated castor oil was studied using conventional and microwave heating. Reactions were followed by measuring the acid number and reaction products were characterized by FTIR and 1H-NMR. A kinetic model, that fit the experimental data, was found. The reaction was non-catalytic, first-order with respect to hydroxyl-groups concentration and first-order with respect to acid-groups concentration. This reaction proceeded more quickly when microwaves were used and showed the presence of non-thermal effects of microwave heating, which were evidenced by the 10% decrease in the activation energy and the 182% increase in the pre-exponential factor.